Diversity and distribution of mollusks at three zones of mangrove in Pejarakan, Bali, Indonesia - I KETUT GINANTRA (MBI & UNS Solo, 2020)
Abstract. Ginantra IK, Muksin IK, Suaskara IBM, Joni M. 2020. Diversity and distribution of mollusks at three zones of mangrove in Pejarakan, Bali, Indonesia. Biodiversitas 21: 4636-4643. The diversity of mangrove species in mangrove zonations on the coast of Pejarakan plays an important role in the existence of faunal diversity, including those from mollusks. Mollusks are the dominant phylum associated with mangrove habitats, in addition to the species of the Crustacean subphylum. This research aimed to determine the diversity of mollusks and their distribution patterns in three mangrove zones in Pejarakan, Buleleng District, Bali Province, Indonesia. Data collection was conducted by establishing sampling plots across three mangrove zones, i.e. seaward zone, middle zone, and landward zone. There were 23 sampling plots in total with size of each plot was 1x1m. The species and number of individuals of each species of mollusks were recorded in each quadrat plot. The diversity of mollusks was calculated using the Shannon-Wiener index, evenness index, and dominance index, while the pattern of distribution of mollusks was measured using the Morisita index. The results of the study found 27 species of mollusks, consisting of 19 species from Gastropods group, 7 species from Bivalvia group and 1 species from Polyplacophora (chiton). The seaward zone showed the highest species diversity, while the landward zone had the lowest. Terebralia palustris had the highest abundance with 217 individuals/m2 and was distributed in the three mangrove zones. Planaxis sulcatus showed the highest abundance (87 ind./m2) in the seaward zone, and Telescopium telescopium showed a fairly high abundance and were distributed in the mid zone and the landward zone. In general, mollusks in the mangrove area of Pejarakan was distributed in a group/clustered pattern. The data from this research can serve as a reference in mangrove forest conservation efforts and mangrove forest used for ecotourism.